New Five Year Plan (1978-83) Sector - Economic Services, General Services Draft Annual Plan 1978-79 Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1978)
As the volume of planning work at the Administration's level has multiplied manifold, it has became imperative to suitably strengthen the present Planning machinery which consists oi skeleton staff only in order to cope-up with the ever increasing volume of Planning work by appointing minimum additional staff and providing other material and equipment.
Andaman and Nicobar Administration